Culturally sustaining and translingual approaches to teaching bi/multilingual writers - Harvey-Torres, Rosalyn; LaFuerte, Clint; Landeros, Judith (New Jersey: Wiley Company, 2023)
This research team offers portraits of two Latina bilingual elementary school teachers as they engage students in culturally sustaining writer's workshops in Spanish and English.
Keywords: Study and Teaching. -- Multilingual writers